2019
DOI: 10.1128/mbio.02563-18
|View full text |Cite
|
Sign up to set email alerts
|

AtrR Is an Essential Determinant of Azole Resistance in Aspergillus fumigatus

Abstract: Aspergillosis associated with azole-resistant Aspergillus fumigatus has a mortality rate that can approach 90% in certain patient populations. The best-understood avenue for azole resistance involves changes in the cyp51A gene that encodes the target of azole drugs, lanosterol α-14 demethylase. The most common azole resistance allele currently described is a linked change corresponding to a change in the coding sequence of cyp51A and a duplication of a 34-bp region in the promoter leading to a tandem repeat (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(146 citation statements)
references
References 42 publications
9
113
1
1
Order By: Relevance
“…Expression and/or upregulation of ATP-binding cassette (ABC) transporters is also frequently associated with azole resistance in fungi (Lamping et al, 2009;Panapruksachat et al, 2016;Watanasrisin et al, 2016;Paul et al, 2019). In A. fumigatus, the AtrR TF binds to, and regulates, both cyp51A and the ABC transporter abcG1.…”
Section: Cyp51a Cyp51b Cyp51cmentioning
confidence: 99%
“…Expression and/or upregulation of ATP-binding cassette (ABC) transporters is also frequently associated with azole resistance in fungi (Lamping et al, 2009;Panapruksachat et al, 2016;Watanasrisin et al, 2016;Paul et al, 2019). In A. fumigatus, the AtrR TF binds to, and regulates, both cyp51A and the ABC transporter abcG1.…”
Section: Cyp51a Cyp51b Cyp51cmentioning
confidence: 99%
“…The repeat is 34-, 46-, or 53-bp long and located approximately 300 bp upstream of the cyp51A start codon. The region contains AtrR-and SrbA-binding elements [6][7][8] , which regulate cyp51A expression. In addition to the duplication of the region upregulating cyp51A expression, amino acid substitutions contribute to azole resistance, except in the TR53-type strain, which contains no substitution in cyp51A.…”
Section: Emergence Of Azole-resistant a Fumigatus In The Environmentmentioning
confidence: 99%
“…We have shown that loss of the NCT complex leads to a large increase in MIC to the azoles, most notably for posaconazole where we observed a shift in MIC from 0.25 mg/L to >16 mg/L. This phenotype is associated with transcriptional dysregulation of the ergosterol biosynthetic pathway directly and indirectly via srbA 10 , atrR 11,15 and hapC 12 , an increase in cellular ergosterol levels (c. 1.6-fold) and an increase in levels of the Cdr1B azole transporter (2.4-fold) (see model in Fig. 9).…”
Section: Discussionmentioning
confidence: 77%
“…The repeat duplicates the DNA-binding site leading to SrbA-mediated upregulation of cyp51A and a concomitant increase in azole resistance. AtrR, a Zn2-Cys6 transcription factor, also positively regulates sterol biosynthesis and directly binds the cyp51A promoter at the TR site, and additionally the promoter of an azole exporter, cdr1B 11,15 . The CCAAT-binding domain complex CBC, a heterotrimer comprising HapB, HapC and HapE, is a negative regulator of sterol biosynthesis directly binding the promoters of 14 ergosterol biosynthetic genes, including cyp51A 12 .…”
mentioning
confidence: 99%